Discovery and hit-to-lead optimization of 2, 6-diaminopyrimidine inhibitors of interleukin-1 receptor-associated kinase 4. Issue 9 (1st May 2015) - McElroy, William T.; Michael Seganish, W.; Jason Herr, R.; Harding, James; Yang, Jinhai; Yet, Larry; Komanduri, Venukrishnan; Prakash, Koraboina Chandra; Lavey, Brian; Tulshian, Deen; Greenlee, William J.; Sondey, Christopher; et al.
Graphical abstract